Exploring the teaching and learning of moral education in Melaka secondary school - Tham, Jia Hao; Mustakim, Siti Salina (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Moral Education is a compulsory course for non-Muslim students in Malaysia education system. Started from primary schools until secondary schools, students will study Moral Education for 11 years. The aim of Moral Education is to develop a disciplined, cultured and united individual. This curriculum is significance in the multi-cultural society to unite the country. However, teaching and learning activities are the main factor in succeeding the curriculum. This paper will discusses the background of Moral Education, explore the teaching and learning activities in a secondary school and propose suitable activities for moral class.